2016
DOI: 10.1016/j.tws.2016.04.014
|View full text |Cite
|
Sign up to set email alerts
|

Fire performance of innovative steel-concrete composite columns using high strength steels

Abstract: This paper presents the results of a numerical investigation on strategies for enhancing the fire behaviour of concrete-filled steel tubular (CFST) columns by using inner steel profiles such as circular hollow sections (CHS), HEB profiles or embedded steel core profiles. A three-dimensional finite element model is developed for that purpose, which is capable for representing the various types of sections studied and the nonlinear behaviour of the materials at elevated temperatures. High strength steel is consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 35 publications
(42 reference statements)
1
16
0
Order By: Relevance
“…It is therefore shown that SRCFSST columns offer a good solution for enhancing the fire resistance of traditional CFST or CFSST columns, but the cross-sectional areas of the outer tube and inner steel profile should be chosen carefully to find the optimal balance between ambient temperature performance and fire resistance. Similar conclusions were reached by Espinos et al 31 for traditional CFST columns with embedded HEB profiles.…”
Section: Comparisons Between the Composite Columns With The Same Steesupporting
confidence: 88%
“…It is therefore shown that SRCFSST columns offer a good solution for enhancing the fire resistance of traditional CFST or CFSST columns, but the cross-sectional areas of the outer tube and inner steel profile should be chosen carefully to find the optimal balance between ambient temperature performance and fire resistance. Similar conclusions were reached by Espinos et al 31 for traditional CFST columns with embedded HEB profiles.…”
Section: Comparisons Between the Composite Columns With The Same Steesupporting
confidence: 88%
“…Recent studies used NC as filling mixture in the HSC because OPC is the most consumed material in construction industry because of the availability (Espinos et al, 2015b;Du et al, 2017;Liu et al, 2017;Espinos et al, 2014;Liew et al, 2016;Espinos et al, 2016). The study on the performance of CFHS is actively conducted, especially in countries that are exposed to fire and earthquake (Buchanan and Abu, 2017).…”
Section: Filling Materialsmentioning
confidence: 99%
“…The numerical model was developed using ABAQUS [5]. Numerical investigations of concrete-steel composite columns have been reported in [6][7][8][9][10]. In this study, four-noded doubly curved shell elements with reduced integration (S4R) were employed to model the metal tubes, while eight-noded brick elements with three translational degrees of freedom at each node (C3D8R) were used for the concrete.…”
Section: Description Of Finite Element Modelmentioning
confidence: 99%